1982
DOI: 10.1111/j.1744-313x.1982.tb00981.x
|View full text |Cite
|
Sign up to set email alerts
|

REGULATION OF EXPERIMENTAL AUTOIMMUNE THYROIDITIS: INFLUENCE OF NON‐H‐2 GENES

Abstract: SUMMARY Experiments were conducted to investigate the non‐H‐2 genetic effects on experimental autoimmune thyroiditis (EAT). Strains having C3H or BALB backgroud in general produced higher autoimmune responses to mouse thyroglobulin (MTg) than the B10 or A strains. Comparisons of C3H and B10 congenic strains carrying similar H‐2 haplotypes demonstrated that the C3H congenics had significantly higher MTg antibody titres and more severe thyroid damage, even when the strains carry the low responder H‐2 haplotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 29 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Susceptibility to EAT in mice was traditionally thought to be influenced only by the mouse class II MHC genes (39,56). However, further studies have shown that other genes outside the MHC gene complex must be involved in the susceptibility to EAT in mice (57,58). Moreover, one study (59) has shown that induction of EAT by immunization with Tg from different strains of mice had a profound effect on the degree of thyroiditis developed, suggesting that alterations in the sequence͞structure of mTg were important for the development of EAT.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to EAT in mice was traditionally thought to be influenced only by the mouse class II MHC genes (39,56). However, further studies have shown that other genes outside the MHC gene complex must be involved in the susceptibility to EAT in mice (57,58). Moreover, one study (59) has shown that induction of EAT by immunization with Tg from different strains of mice had a profound effect on the degree of thyroiditis developed, suggesting that alterations in the sequence͞structure of mTg were important for the development of EAT.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model of experimental autoimmune thyroiditis (EAT), induced by thyroglobulin, genes within and without the major histocompatibility complex (MHC) locus have been implicated in the regulation of the disease process (Kuppers et al 1988 a;Vladutiu and Rose, 1971;Tomazic et al 1974;Ben-Nun et al, 1980;Beisel et al 1982aBeisel et al , 1982b. Genetic loci outside the MHC locus that influence EAT have not been mapped.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on Tg-mediated EAT localized control of susceptibility in the H-2A region of the H-2k haplotype (Beisel et al 1982a). Genetic influences on EAT development have also been attributed to the K or the D region of the H-2 complex (Maron and Cohen 1979;Ben-Nun et al 1980;Maron and Cohen 1980;Kong et al 1979) and to non-H-2 genes (Beisel et al 1982b). …”
mentioning
confidence: 99%